elaboration and characterzation of NI-CeO2 coating :evaluation of anticorrosion properties - gharbi amira (My University, 2025)
Nickel coatings are widely recognized for their intrinsic corrosion and wear resistance, high hardness, and excellent mechanical integrity. However, under prolonged exposure to chloride-rich conditions, nickel coatings can suffer from localized corrosion, cracking, and delamination.To overcome these challenges, Ni coatings performance can be enhanced through the incorporation of advanced nanomaterials. Therefore, in the present study, graphene (Gr) nanosheets were synthesized via controlled electrochemical exfoliation and a novel Ni-CeO2-Gr ternary nanocomposite coating was elaborated on copper substratesby the incorporation of synthetized graphene nanosheets and cerium oxide (CeO2) nanoparticles into the nickel matrix via co-electrodeposition and under identical optimized electrodeposition parameters (watts bath, 55°C, 0.1g/L SDS at 55 mA/cm2). The elaborated coatings were characterized using optical microscopy, scanning electron microscopy (SEM) coupled with energy-dispersive spectrometry (EDS), Raman spectroscopy, X-ray diffraction (XRD), Vickers microhardness and micro-scratch tests. While the electrochemical properties of the coatings were evaluated by electrochemical impedance (EIS) and DC-polarization measurements in 0.5 M NaCl. SEM-EDS, Raman, and XRD analysis confirmed the successful synthesis of high-quality single layer graphene. The incorporation of CeO2 nanoparticles and graphene nanosheets into the nickel coating matrix was confirmed by SEM‑EDS, XRD and Raman spectroscopy. it was found that the ternary Ni-CeO2-Gr coating achieved an outstanding microhardness of 915.6 HV, which is 3.5 times higher than conventional Ni coatings (265 HV) and exhibited a significant increase in critical load, indicative of superior cohesive strength and resistance to delamination. Furthermore, electrochemical impedance spectroscopy (EIS) and DC‑polarization measurements in 0.5 M NaCl demonstrated that the Ni-CeO2-Gr composite possessed the highest polarization resistance (544 kΩ.cm2) compared to pure Ni (30 kΩ.cm2) and both binary composites. This remarkable enhancement is due to the synergistic effect of the graphene’s impermeable lamellar structure and CeO2 duplex layer within the Ni matrix, forming a robust anticorrosion barrier.  the results confirm that optimized electrodeposition parameters combined with duplex nanomaterial reinforcement offer valuable insights into the designing highly efficient advanced nanocomposite coatings for corrosion protectionfor demanding industrial applications. Key words: Ni-CeO2NPs-Graphene nanosheets, Ternary nanocomposites Coatings, Co-electrodeposition, Corrosion resistance, Surface characterization, Electrochemical exfoliation, EIS, DC-polarization, Vickers microhardness, scratch test
Les revêtements à base de nickel sont largement reconnus pour leur résistance intrinsèque à la corrosion et à l’usure, leur dureté élevée et leur excellente intégrité mécanique. Cependant, exposés de façon prolongée à des milieux riches en chlorures, ces revêtements peuvent subir une corrosion localisée, la formation de fissures et un délaminage. Pour pallier ces limites, la performance des revêtements de Ni peut être améliorée par l’incorporation de nanomatériaux avancés. Ainsi, dans la présente étude, des feuillets de graphène (Gr) ont été synthétisés par exfoliation électrochimique contrôlée.En utilisant un bain Watts optimisé (55 °C, 0,1 g/L SDS, 55 mA/cm2), un nouveau revêtement nanocomposite ternaire Ni-CeO2-Gr a été élaboré sur substrats en cuivre via co électrodéposition de ces nanofeuilles de graphène et de nanoparticules d’oxyde de cérium (CeO2) dans la matrice de nickel. Les revêtements obtenus (Ni pur, Ni-Gr, Ni-CeO2 et Ni-CeO2-Gr) ont été caractérisés par microscopie optique, microscopie électronique à balayage couplée à spectrométrie par dispersion d’énergie (SEM EDS), spectroscopie Raman, diffraction des rayons X (XRD), microdureté Vickers et essais de micro rayure, tandis que leurs propriétés électrochimiques ont été évaluées par spectroscopie d’impédance électrochimique (EIS) et polarisation DC en NaCl 0,5 M. Les analyses SEM EDS, XRD et Raman ont confirmé la synthèse d’un graphène mono¬couche de haute qualité et l’intégration homogène des nanoparticules de CeO2 et des nanofeuillesde Gr dans la matrice de nickel. Il en ressort que le revêtement ternaire Ni-CeO2-Gr atteint une microdureté remarquable de 915,6 HV, soit 3,5 fois celle d’un Ni conventionnel (265 HV), et présente une charge critique accrue, témoignant d’une cohésion interne supérieure et d’une meilleure résistance au délaminage. De plus, la spectroscopie d’impédance électrochimique « SIE » et les mesures de polarisation ont mis en évidence une résistance à la polarisation de 544 kΩ.cm2 pour Ni-CeO2-Gr, contre 30 kΩ.cm2 pour Ni pur et des valeurs intermédiaires pour les composites binaires. Cette nette amélioration résulte de la synergie entre la structure lamellaire imperméable du graphène et la couche duplex de CeO2,formant une barrière anticorrosion robuste. Les résultats confirment que l’association de paramètres d’électrodéposition optimisés et du renforcement par nanomatériaux duplex permet de concevoir des revêtements nanocomposites avancés pour la protection anticorrosion dans des applications industrielles exigeantes. Mots clés :nanofeuilles de graphène, revêtements nanocomposites ternaires, co électrodéposition, résistance à la corrosion, caractérisation de surface, exfoliation électrochimique, SIE, polarisationstattionnaire, microdureté Vickers, essai de rayure.
Keywords: Key words: Ni-CeO2NPs-Graphene nanosheets; Ternary nanocomposites Coatings; Co-electrodeposition; Corrosion resistance; Surface characterization; Electrochemical exfoliation; EIS; DC-polarization; Vickers microhardness; scratch test; الكلمات المفتاحية: جسيمات Ni- CeO2النانوية- صفائح الجرافين النانوية، طلاءات نانوية مُركّبة ثلاثية، الترسيب الكهربائي المُشترك،مقاومة التآكل، توصيف السطح، التقشير الكهربائي، EIS،استقطاب التيار المستمر، صلادة فيكرز، اختبار الخدش.; Mots clés :nanofeuilles de graphène; revêtements nanocomposites ternaires; co électrodéposition; résistance à la corrosion; caractérisation de surface; exfoliation électrochimique; SIE; polarisationstattionnaire; microdureté Vickers; essai de rayure.